The Australian work exposures study: Prevalence of occupational exposure to diesel engine exhaust - Peters, S.; Carey, Renee; Driscoll, T.; Glass, D.; Benke, G.; Reid, Alison; Fritschi, L. (Oxford University Press, 2015)
Background: Diesel engines are widely used in occupational settings. Diesel exhaust has been classified as a lung carcinogen, but data on number of workers exposed to different levels of diesel exhaust are not available in Australia. The aim of this study was to estimate the current prevalence of exposure to diesel engine exhaust in Australian workplaces. Methods: A cross-sectional survey of Australian males and females (18–65 years old) in current paid employment was undertaken. Information about the respondents’ current job and various demographic factors was collected in a telephone interview using the web-based tool OccIDEAS. Semi-quantitative occupational exposure levels to diesel exhaust were assigned using programmed decision rules and numbers of workers exposed in Australia in 2011 were estimated. We defined substantial exposure as exposed at a medium or high level, for at least 5h per week. Results: Substantial occupational exposure to diesel exhaust was experienced by 13.4% of the respondents in their current job. Exposure prevalence varied across states, ranging from 6.4% in the Australian Capital Territory to 17.0% in Western Australia. Exposures occurred mainly in the agricultural, mining, transport and construction industries, and among mechanics. Men (20.4%) were more often exposed than women (4.7%). Extrapolation to the total working population indicated that 13.8% (95% confidence interval 10.0–20.4) of the 2011 Australian workforce were estimated to be substantially exposed to diesel exhaust, and 1.8% of the workers were estimated to experience high levels of exposures in their current job.Conclusion: About 1.2 million Australian workers were estimated to have been exposed to diesel exhaust in their workplace in 2011. This is the first study to describe the prevalence of occupational diesel exhaust exposure in Australia and will enable estimation of the number of lung cancers attributable to diesel exhaust exposure in the workplace.